The Multi-Modal Risk Analysis and Medical Prevention of Lumbar Degeneration, Fatigue, and Injury Based on FEM/BMD for Elderly Chinese Women Who Act as Stay-Home Grandchildren Sitters - Li, Na; Cavagnaro, María José; Xiong, Kun; Du, Xianping; Shi, Jian (Frontiers in Public Health, 2021)
Background: An increasing number of Chinese elderly women stay at home and act as grandchildren sitters. In consequence of the frequent load-bearing, chronic lumbar fatigue probably caused a higher risk of lumbar degeneration, fatigue, and injury which has become one of the most important aging and health problems in China. In this study, a multi-mode lumbar finite element model (FEM) with specific bone mineral density (BMD) were developed and validated for further spine injury prevention and control. Methods: The material properties of lumbar vertebra were modified according to degenerated bone mineral density, and geometry was adjusted based on intervertebral disc height. The motion of lifting children was simulated by a 76 year-old Chinese women's FEM, and the stress distribution was calculated and predicted. Results: The pressure of L5-S intervertebral disc in the bending 3-year-old dummy lifting posture was significantly higher than the same posture without lifting, the maximum effective stress of endplate cartilage in the upright child lifting posture was 1.6 times that of the bending without lifting posture. And the fatigue risk limitation frequency of the upright with dummy posture was predicted with the functional equation of fatigue and stress which was deduced by genetic algorithm, which combined with the effective stress of lumbar vertebrae spongy bone calculated from FEM. Conclusions: The child-lifting motion could increase the risk of lumbar degeneration, fatigue, and injury in elderly women, and they should keep below the frequency limit of the motion of lifting children in their daily life. This study could put forward scientific injury prevention guidance to Chinese elderly women who lift children in daily life frequently.